REGIONALIZATION OF JAVA ISLAND: POVERTY, PANDEMIC AND GENDER - Estuning Tyas Wulan Mei; Lutfi Mutaali; Muhammad Baiquni; R Rijanta; Bambang Sri Eko Prakoso; Joko Christanto; Dodi Widiyanto; Alia Fajarwati; Surani Hasanati; Agung Satriyo Nugroho; Idea Wening Nurani; Rizki Adriadi Ghiffari; Didik Sri Wahyudi; Adji Saiddinullah; Muhammad Galang Ramadhan Al Tumus; Dhia Fauzia Rahman (JURNAL GEOGRAFI, 2022)
Among various issues on regional development planning in Indonesia, the vast coverage area and its regional diversity become one of main challenges. Regionalization is one of spatial techniques that can be used to facilitate regional development planning process. This study aims to analyze regionalization of Indonesia with a focus on Java Island by highlighting the main contemporary issues including poverty, COVID-19 pandemic, and gender. This paper draws the conditions of poverty, the cases of the COVID-19 pandemic and the needs of gender-based development in 119 regencies/cities on the island of Java using spatial distribution analysis. The results of the analysis show that the distribution of the percentage of the poor and the poverty line in Java forms a clustered pattern. This also happened in the case of COVID-19 where the high concentration of cases was around DKI Jakarta and DI Yogyakarta. As for the gender aspect, there is a tendency for a scattered pattern for the value of the gender development index, although there are some areas with high values (H-H quadrant) and low values (L-L quadrant). In general, the use of regional analysis may facilitate the identification of spatial phenomena, their distribution and the patterns formed, therefore it can be used for determining suitable regional policies.Keywords: Java Island, Regionalization, Poverty, COVID-19 Pandemic, Gender